The Influence of Johnny’s Communication Center YouTube Vlogs on English Learning Interest Among NCTzen in Indonesia - Azhara Aurel Varizky; Devinta Puspita Ratri (Publikasi Indonesia, 2024)
This study aims to determine whether Johnny's Communication Center YouTube vlogs have an influence on English learning interest among NCTzen in Indonesia. This article uses a quantitative approach and survey research method. The data collection technique used a questionnaire distributed through social media X (Twitter) to approximately 100 NCTzen community who are still in high school and watch Johnny's Communication Center vlogs on YouTube. This study found that Johnny's Communication Center YouTube vlogs significantly enhance interest in learning English among NCTzens in Indonesia, with a positive regression coefficient of 1.391. The results highlight the potential of leveraging social media and K-pop idols to develop effective educational strategies for young learners.